Pattern of Divorce in Early Marriage: (Case Study in Taman Ayu Village, Gerung District) - Muh. Wakidillaisi (Jurnal Sosial dan Humaniora, 2026)
This study aims to examine the phenomenon of divorce experienced by couples who get married at a young age in Bongor Hamlet, Taman Ayu Village, Gerung District, West Lombok Regency. Early marriage is a complicated social problem, especially in rural Indonesia, and West Nusa Tenggara is one of the areas with a relatively high incidence rate. This study uses a family sociology approach with a descriptive qualitative method. Data collection was carried out through in-depth interviews with ten informants, consisting of divorced former couples, local community leaders, religious leaders, and officers of the Gerung District Religious Affairs Office (KUA). The results of the study identified five main factors that encourage the occurrence of divorce in early marriage in the region, namely: (1) the psychological and emotional unpreparedness of young couples in managing conflicts that arise in married life; (2) heavy economic burden due to low educational background and limited job opportunities; (3) excessive interference of the extended family in domestic affairs; (4) infidelity triggered by emotional immaturity; and (5) domestic violence (KDRT).